Socialization and Training on Branding and Product Marketing in the Marketplace for MSME Owners in Candipari Region: Sosialisasi dan Pelatihan Branding Serta Pemasaran Produk di Marketplace untuk Pemilik UMKM Daerah Candipari - Widhianingsih, Wiwik; Ariyanti, Novia; Zahro, Reza Tus; Aida, Wafid (Procedia of Social Sciences and Humanities, 2022)
Sidoarjo is an area in Indonesia known as an industrial city. This is evidenced by the many industries that have emerged in Sidoarjo. This industry starts from small MSME (Micro, small, medium enterprise) to large industries. Technological progress is unavoidable in this day and age. This causes those who cannot keep up with technological developments will be eroded and experience natural selection. Especially for MSME (Micro, Small, Medium Enterprise) competition, which is basically a competition to dominate the market with their own products, it will be very difficult if they are not able to master technology. For this reason, we students of community service team 12 carried out socialization and assistance regarding branding and marketing methods. Which aims to provide knowledge that a unique brand name for a product is very important to maintain the product in the market. While the socialization of our method provides knowledge on how to trade in a marketplace like Shopee starting from the advantages to the weaknesses of the marketplace.